Can China’s cross-sectional dispersion of stock returns Cause or influence the herding behaviour of traders in other local markets and China’s trading partners? - Chong, Oiping; Amin Noordin, Bany Ariffin; Matemilola, Bolaji Tunde; McGowan, Carl B. (Elsevier, 2020)
This paper examines the influence of China’s cross-sectional dispersion of returns on local markets, as well as its major trading partners. With the cross-sectional average deviation method, we have reported some significant and insignificant results, as well as for tranquil and turbulent phases of the Chinese stock market. It seems that the cross-sectional dispersion of returns in China has influenced markets in countries in the greater China region and some other Asian countries but not markets in Europe or the United States. Although China’s cross-sectional dispersion of returns plays a role in influencing the country’s trading partners, which are categorised as having high, medium or low trade volumes, it does not cause any of these groups to herd around its market. Thus we conclude that although China is the world's second-largest economy after that of the United States, China's role in stock trading is still unmatched by the United States.